Challenges of the Quality- and Change Management in the Context of Upcoming Social-Industrial Changes (5.0) – Conclusion of a Survey - Hugyi, Milan (International Journal of Engineering and Management Sciences, 2022)
The upcoming industrial-social revolution, which may be called the 5.0, is emphasizing the coordination of the value-creating work of technology (machine) and man. This approach wishes to move towards sustainability, which deserves a significant role in nowadays through the world empathizing the negative effects of the wolrd. During my research I was looking for the answer that how the extended industry 4.0 and its tone be in Hungary via supply chain of the automotive industry. During my research I was looking for the answer that how the extended industry 4.0 be in Hungary and its tune through supply chain of the automotive industry. I also have examined that which changes are justified regarding management systems in interest of efficiency and emphasizing the human capital by leaders interviewed. As a part of qualitative research in-depth expert interviews were interpreted with help of content analysis based on the methodology of grounded theory. The results demonstrate the need to review and change existing processes in order to ensure that the potential of human capital is not lost and that technological development, even more so, is at the service of human resources in order to achieve its efficiency and effectiveness. Among the possible tools we can find the re-structurizing changes of post tracking processes of the audits in management systems providing quality. Furthermore, the practical implementation of multifactorial statistical process control in the evaluation of processed data, which may be one of the essences of industrial (IoT) data.